Synthesis of optimal covert sensor–actuator attackers for discrete-event systems. (May 2023) - Tai, Ruochen; Lin, Liyong; Su, Rong
Abstract: This work introduces an approach for the synthesis of optimal covert sensor–actuator attackers in the context of discrete-event systems (DES). Building upon existing works on optimal supervisor synthesis, on one hand, and the base model construction in the transformation of covert sensor–actuator attacker synthesis to supervisor synthesis, on the other hand, we show how the optimal covert sensor–actuator attacker synthesis problem could be transformed to the optimal supervisor synthesis problem, thus generalizing its logic counterpart. We consider several different types of optimization objectives, such as (1) minimization of attack energy cost, and (2) minimization of time cost to cause damage infliction; for the latter one, asynchronous event firings and concurrent event firings at the plant are both considered. We provide the necessary and sufficient conditions for the existence of an optimal attacker for both the energy minimization case and damage infliction time minimization case. Thus, this work may potentially provide a unified approach for the optimal synthesis of covert sensor–actuator attackers in different setups.